The Relationship Between Emergency Medical Record Completeness And The Timeliness Of BPJS Claims At Wangaya Regional General Hospital, Denpasar - I Wayan Nanda Artautama; Nurul Faidah; I Gusti Agung Ngurah Pradnyantara (CV. AFDIFAL MAJU BERKAH, 2026)
Hospital is a healthcare institution that provides comprehensive health services, including emergency services. The completeness of medical records is one of the indicators of healthcare service quality and plays an important role in administrative processes, including the submission of BPJS claims. This study aims to determine the relationship between the completeness of emergency medical records and the timeliness of BPJS claims at Wangaya Regional General Hospital, Denpasar City. This study used a quantitative method with a cross-sectional design involving a sample of 140 emergency patient medical record files Using a purposive sampling technique. Data were collected through document observation using a medical record completeness checklist and BPJS claim data, then analyzed using the chi-square test. The results showed that the completeness rate of medical records reached 96% complete files and 4% incomplete, while the timeliness of BPJS claims showed that 82.9% of claims were submitted on time and 17.1% were not submitted on time. The statistical test results indicated a significant relationship between the completeness of medical records and the timeliness of BPJS claims (0.000 < 0.05) with a relationship strength of 0.926, which is categorized as a very strong relationship. It can be concluded that the more complete the medical records filled out by healthcare workers, the greater the possibility that BPJS claims can be submitted on time. Therefore, increased discipline and supervision in completing medical records are needed to support the smooth administrative process of claims in hospitals.